Additive for enhancing repairing capacity of asphalt concrete pavement and preparation method of additive
By preparing an additive containing a surface curing agent, heat-transmitting wire, and special filler, the problem of long repair time for asphalt concrete pavement was solved, achieving the effects of rapid repair and enhanced pavement strength.
Patent Information
- Application Number
- CN202411483293.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
AI Technical Summary
Existing asphalt concrete pavement repair additives have a long initial setting time, which leads to extended construction time and increases the probability of road congestion.
An additive that can rapidly solidify and widely penetrate the interior of asphalt was prepared by using a combination of surface coagulant, heat-transmitting wire, styrene-butadiene-styrene block copolymer, antioxidant and UV stabilizer, and by controlling the stirring speed, temperature and time.
It shortens the curing time of road surface repair, reduces the sealing time, improves the strength and stability of the repaired area, and enhances the smoothness and durability of the road.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of asphalt concrete pavement repair, and specifically relates to an additive for enhancing the repairing ability of asphalt concrete pavement and a preparation method thereof. Background Art
[0002] Repairing asphalt pavement is a complex and delicate process that includes cleaning the site, assessing the extent of damage, and applying additives to repair cracks in the pavement.
[0003] Among them, the initial setting time of the additive is generally 4 hours, plus the repair construction time, including: road closure, road cleaning, assessment, road unsealing, etc., the overall time is relatively long, which brings inconvenience to traffic and increases the probability of road congestion. Summary of the invention
[0004] The purpose of the present invention is to provide an additive for enhancing the repairing ability of asphalt concrete pavement and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] The invention provides an additive for enhancing the repairing ability of asphalt concrete pavement. The raw materials for preparing the additive include, by weight, 10-15 parts of a surface coagulant, 10-15 parts of a heat-transmitting wire, 3-9 parts of a surfactant, 6-8 parts of an antioxidant, 3-6 parts of an anti-ultraviolet agent, and 30-40 parts of a styrene-butadiene-styrene block copolymer.
[0007] As a further optimization scheme of the present invention, the preparation process of the surface coagulant is:
[0008] In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, the stirring speed is controlled to be 10-30 rps, the temperature is controlled to be 10-16° C., and the time is controlled to be 10-15 min to obtain a glue mixture;
[0009] The pore-increasing powder and the glue mixture are stirred and mixed, the stirring speed is controlled to be 10-30 rps, the temperature is controlled to be 5-10° C., and the time is controlled to be 10-15 min to obtain a surface coagulant.
[0010] As a further optimization scheme of the present invention, the mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.5.
[0011] As a further optimization scheme of the present invention, the preparation process of the pore-increasing powder is as follows:
[0012] The slaked lime powder and the sodium hydroxide particles are stirred and mixed, and the stirring speed is controlled to be 10-20 and the time is controlled to be 10-15 minutes; wherein the diameter of the slaked lime powder is 30-60 μm, and the diameter of the sodium hydroxide particles is 1-3 mm, to obtain a pore-increasing powder.
[0013] As a further optimization scheme of the present invention, the mass ratio of the slaked lime powder to the sodium hydroxide particles is 4:1.
[0014] As a further optimization scheme of the present invention, the preparation process of the diathermic wire is as follows: melting iron powder and copper powder at high temperature to obtain a metal mixture;
[0015] Pour the graphite fiber into the metal mixture and mix and stir, control the stirring speed to 2-6rps, and control the time to 3-8min to obtain a fiber-metal mixture;
[0016] The fiber metal mixture is poured into a mold to obtain a composite metal sheet with a thickness of 4-6 μm, and the composite metal sheet is sheared by a fiber shearing machine to obtain a heat-transmitting wire with a diameter of 4-6 μm and a length of 1-3 cm.
[0017] As a further optimization scheme of the present invention, the mass ratio of the iron powder, copper powder and graphite fiber filaments is 2:1:0.2.
[0018] A method for preparing the above-mentioned additive for enhancing the repairing ability of asphalt concrete pavement comprises the following steps:
[0019] S1, mixing styrene-butadiene-styrene block copolymer and a surfactant to obtain a permeable filler;
[0020] S2, an antioxidant, an anti-ultraviolet agent and a permeable filler are mixed to obtain a characteristic filler;
[0021] S3. Mix the surface coagulant, the diathermic wire and the special filler to obtain an additive.
[0022] The beneficial effects of the present invention are as follows: the surface coagulant prepared from the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder shortens the time required for the surface of the additive to solidify, and when cracks on the asphalt pavement are repaired, traffic can be opened to traffic at the fastest speed, thereby minimizing the time of road section closure and alleviating the pressure of road congestion; in addition, the diathermic wire prepared from iron powder, copper powder and graphite fiber wire maximizes the area over which the additive penetrates and extends into the interior of the asphalt through the cracks, thereby being able to combine more widely with the asphalt, thereby enhancing the overall strength and stability of the repaired part, helping to better fill cracks, potholes and other defects, and improving the flatness and durability of the road. DETAILED DESCRIPTION
[0023] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0024] 1. Materials
[0025] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0026] In the present invention:
[0027] The surfactant used was 1631 hexadecyltrimethylammonium chloride produced by Guangzhou Zongheng Chemical Co., Ltd.
[0028] The antioxidant used is BASF;
[0029] The anti-ultraviolet agent used is TINUVIN326 ultraviolet absorber 326 from BASF of Germany.
[0030] 2. Embodiment
[0031] Example 1
[0032] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 10 parts of surface coagulant, 10 parts of diathermic wire, 3 parts of surfactant, 6 parts of antioxidant, 3 parts of anti-ultraviolet agent, and 30 parts of styrene-butadiene-styrene block copolymer;
[0033] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0034] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0035] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to be 10 rps, and control the time to be 10 min; wherein the diameter of the slaked lime powder is 30 μm, and the diameter of the sodium hydroxide particles is 1 mm, to obtain a pore-increasing powder;
[0036] Surface coagulant: In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, and the stirring speed is controlled to be 10 rps, the temperature is controlled to be 10°C, and the time is controlled to be 10 min to obtain a glue mixture; the pore-increasing powder and the glue mixture (the mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.5) are stirred and mixed, and the stirring speed is controlled to be 10 rps, the temperature is controlled to be 5°C, and the time is controlled to be 10 min to obtain a surface coagulant;
[0037] Diathermy wire: melt iron powder and copper powder at high temperature to obtain a metal mixture; pour graphite fiber into the metal mixture (the mass ratio of iron powder, copper powder and graphite fiber is 2:1:0.2) for mixing and stirring, control the stirring speed to 2rps, and control the time to 3min to obtain a fiber metal mixture; pour the fiber metal mixture into a mold to obtain a composite metal sheet with a thickness of 4μm, and cut the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 4μm and a length of 1cm;
[0038] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0039] Example 2
[0040] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 13 parts of a surface coagulant, 13 parts of a diathermic wire, 6 parts of a surfactant, 7 parts of an antioxidant, 5 parts of an anti-ultraviolet agent, and 35 parts of a styrene-butadiene-styrene block copolymer;
[0041] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0042] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0043] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to be 15 rps, and control the time to be 13 min; wherein the diameter of the slaked lime powder is 45 μm, and the diameter of the sodium hydroxide particles is 2 mm, to obtain a pore-increasing powder;
[0044] Surface coagulant: In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 13°C, and the time is controlled to be 13 min to obtain a glue mixture; the pore-increasing powder and the glue mixture (the mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.5) are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 8°C, and the time is controlled to be 13 min to obtain a surface coagulant;
[0045] Diathermy wire: melt iron powder and copper powder at high temperature to obtain a metal mixture; pour graphite fiber into the metal mixture (the mass ratio of iron powder, copper powder and graphite fiber is 2:1:0.2) for mixing and stirring, control the stirring speed to 4rps, control the time to 6min, and obtain a fiber metal mixture; pour the fiber metal mixture into a mold to obtain a composite metal sheet with a thickness of 5μm, and cut the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 5μm and a length of 2cm;
[0046] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0047] Example 3
[0048] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 15 parts of surface coagulant, 15 parts of diathermic wire, 9 parts of surfactant, 8 parts of antioxidant, 6 parts of anti-ultraviolet agent, and 40 parts of styrene-butadiene-styrene block copolymer;
[0049] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0050] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0051] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to 20 rps, and control the time to 15 min; wherein the diameter of the slaked lime powder is 60 μm, and the diameter of the sodium hydroxide particles is 3 mm, to obtain a pore-increasing powder;
[0052] Surface coagulant: In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, and the stirring speed is controlled to be 30 rps, the temperature is controlled to be 16°C, and the time is controlled to be 15 min to obtain a glue mixture; the pore-increasing powder and the glue mixture (the mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.5) are stirred and mixed, and the stirring speed is controlled to be 30 rps, the temperature is controlled to be 10°C, and the time is controlled to be 15 min to obtain a surface coagulant;
[0053] Diathermy wire: melt iron powder and copper powder at high temperature to obtain a metal mixture; pour graphite fiber into the metal mixture (the mass ratio of iron powder, copper powder and graphite fiber is 2:1:0.2) for mixing and stirring, control the stirring speed to 6rps, and control the time to 8min to obtain a fiber metal mixture; pour the fiber metal mixture into a mold to obtain a composite metal sheet with a thickness of 6μm, and cut the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 6μm and a length of 3cm;
[0054] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0055] Comparative Example 1
[0056] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 13 parts of a surface coagulant, 13 parts of a diathermic wire, 6 parts of a surfactant, 7 parts of an antioxidant, 5 parts of an anti-ultraviolet agent, and 35 parts of a styrene-butadiene-styrene block copolymer;
[0057] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0058] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0059] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to be 15 rps, and control the time to be 13 min; wherein the diameter of the slaked lime powder is 45 μm, and the diameter of the sodium hydroxide particles is 2 mm, to obtain a pore-increasing powder;
[0060] Surface coagulant: In a sealed environment, the pore-increasing powder and the α-cyanoacrylate glue solution (the mass ratio of the α-cyanoacrylate glue solution to the pore-increasing powder is 6.9:0.6) are stirred and mixed, and the stirring speed is controlled to 20 rps, the temperature is controlled to 8°C, and the time is controlled to 13 min to obtain a surface coagulant;
[0061] Diathermy wire: melt iron powder and copper powder at high temperature to obtain a metal mixture; pour graphite fiber into the metal mixture (the mass ratio of iron powder, copper powder and graphite fiber is 2:1:0.2) for mixing and stirring, control the stirring speed to 4rps, control the time to 6min, and obtain a fiber metal mixture; pour the fiber metal mixture into a mold to obtain a composite metal sheet with a thickness of 5μm, and cut the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 5μm and a length of 2cm;
[0062] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0063] Comparative Example 2
[0064] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 13 parts of a surface coagulant, 13 parts of a diathermic wire, 6 parts of a surfactant, 7 parts of an antioxidant, 5 parts of an anti-ultraviolet agent, and 35 parts of a styrene-butadiene-styrene block copolymer;
[0065] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0066] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0067] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to be 15 rps, and control the time to be 13 min; wherein the diameter of the slaked lime powder is 45 μm, and the diameter of the sodium hydroxide particles is 2 mm, to obtain a pore-increasing powder;
[0068] Surface coagulant: In a sealed environment, the pore-increasing powder and the anaerobic adhesive solution (the mass ratio of the anaerobic adhesive solution to the pore-increasing powder is 5:1.5) are stirred and mixed, and the stirring speed is controlled to 20 rps, the temperature is controlled to 8°C, and the time is controlled to 13 min to obtain the surface coagulant;
[0069] Diathermy wire: melt iron powder and copper powder at high temperature to obtain a metal mixture; pour graphite fiber into the metal mixture (the mass ratio of iron powder, copper powder and graphite fiber is 2:1:0.2) for mixing and stirring, control the stirring speed to 4rps, control the time to 6min, and obtain a fiber metal mixture; pour the fiber metal mixture into a mold to obtain a composite metal sheet with a thickness of 5μm, and cut the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 5μm and a length of 2cm;
[0070] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0071] Comparative Example 3
[0072] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 13 parts of a surface coagulant, 13 parts of a diathermic wire, 6 parts of a surfactant, 7 parts of an antioxidant, 5 parts of an anti-ultraviolet agent, and 35 parts of a styrene-butadiene-styrene block copolymer;
[0073] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0074] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0075] Surface coagulant: In a sealed environment, an anaerobic adhesive solution and an α-cyanoacrylate adhesive solution (the mass ratio of the anaerobic adhesive solution to the α-cyanoacrylate adhesive solution is 1.1:6.4) are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 13° C., and the time is controlled to be 13 min to obtain a surface coagulant;
[0076] Diathermy wire: melt iron powder and copper powder at high temperature to obtain a metal mixture; pour graphite fiber into the metal mixture (the mass ratio of iron powder, copper powder and graphite fiber is 2:1:0.2) for mixing and stirring, control the stirring speed to 4rps, control the time to 6min, and obtain a fiber metal mixture; pour the fiber metal mixture into a mold to obtain a composite metal sheet with a thickness of 5μm, and cut the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 5μm and a length of 2cm;
[0077] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0078] Comparative Example 4
[0079] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 13 parts of a surface coagulant, 13 parts of a diathermic wire, 6 parts of a surfactant, 7 parts of an antioxidant, 5 parts of an anti-ultraviolet agent, and 35 parts of a styrene-butadiene-styrene block copolymer;
[0080] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0081] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0082] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to be 15 rps, and control the time to be 13 min; wherein the diameter of the slaked lime powder is 45 μm, and the diameter of the sodium hydroxide particles is 2 mm, to obtain a pore-increasing powder;
[0083] Surface coagulant: In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 13°C, and the time is controlled to be 13 min to obtain a glue mixture; the pore-increasing powder and the glue mixture (the mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.5) are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 8°C, and the time is controlled to be 13 min to obtain a surface coagulant;
[0084] Diathermy wire: melt copper powder at high temperature to obtain molten metal; pour graphite fiber into the molten metal (the mass ratio of copper powder to graphite fiber is 2.6:0.6) for mixing and stirring, control the stirring speed to 4rps, and control the time to 6min to obtain a fiber-metal mixed liquid; pour the fiber-metal mixed liquid into a mold to obtain a composite metal sheet with a thickness of 5μm, and shear the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 5μm and a length of 2cm;
[0085] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0086] Comparative Example 5
[0087] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 13 parts of a surface coagulant, 13 parts of a diathermic wire, 6 parts of a surfactant, 7 parts of an antioxidant, 5 parts of an anti-ultraviolet agent, and 35 parts of a styrene-butadiene-styrene block copolymer;
[0088] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0089] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0090] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to be 15 rps, and control the time to be 13 min; wherein the diameter of the slaked lime powder is 45 μm, and the diameter of the sodium hydroxide particles is 2 mm, to obtain a pore-increasing powder;
[0091] Surface coagulant: In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 13°C, and the time is controlled to be 13 min to obtain a glue mixture; the pore-increasing powder and the glue mixture (the mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.5) are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 8°C, and the time is controlled to be 13 min to obtain a surface coagulant;
[0092] Diathermy wire: melt iron powder at high temperature to obtain molten metal; pour graphite fiber into the molten metal (the mass ratio of iron powder to graphite fiber is 2.9:0.3) for mixing and stirring, control the stirring speed to 4rps, and control the time to 6min to obtain a fiber-metal mixed liquid; pour the fiber-metal mixed liquid into a mold to obtain a composite metal sheet with a thickness of 5μm, and shear the composite metal sheet with a fiber shearing machine to obtain a diathermy wire with a diameter of 5μm and a length of 2cm;
[0093] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0094] Comparative Example 6
[0095] An additive for enhancing the repairing ability of asphalt concrete pavement, wherein the raw materials for its preparation include, by weight: 13 parts of a surface coagulant, 13 parts of a diathermic wire, 6 parts of a surfactant, 7 parts of an antioxidant, 5 parts of an anti-ultraviolet agent, and 35 parts of a styrene-butadiene-styrene block copolymer;
[0096] The styrene-butadiene-styrene block copolymer and a surfactant are mixed to obtain a permeable filler;
[0097] Antioxidants, UV inhibitors and permeable fillers are mixed to obtain characteristic fillers;
[0098] Pore-increasing powder: stir and mix slaked lime powder and sodium hydroxide particles (the mass ratio of slaked lime powder to sodium hydroxide particles is 4:1), control the stirring speed to be 15 rps, and control the time to be 13 min; wherein the diameter of the slaked lime powder is 45 μm, and the diameter of the sodium hydroxide particles is 2 mm, to obtain a pore-increasing powder;
[0099] Surface coagulant: In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 13°C, and the time is controlled to be 13 min to obtain a glue mixture; the pore-increasing powder and the glue mixture (the mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.5) are stirred and mixed, and the stirring speed is controlled to be 20 rps, the temperature is controlled to be 8°C, and the time is controlled to be 13 min to obtain a surface coagulant;
[0100] Diathermy wire: Iron powder and copper powder are melted at high temperature to obtain a metal mixture, which is poured into a mold to obtain a composite metal sheet with a thickness of 4-6 μm, and the composite metal sheet is sheared with a fiber shearing machine to obtain a diathermy wire with a diameter of 5 μm and a length of 2 cm;
[0101] The surface coagulant, the diathermic wire and the special filler are mixed to obtain the additive.
[0102] III. Methods
[0103] 1. Surface solidification experiment
[0104] 1.1 Experimental Materials
[0105] Asphalt blocks: 30 pieces (length * width * height: 1 * 1 * 1m) (the same surface of 10 asphalt blocks is opened with cracks of length * width * depth: 30 * 15 * 15cm);
[0106] 1.2 Experimental procedures
[0107] ① Take 5 portions of the additives prepared in Examples 1-3 and Comparative Examples 1-3, each with a volume of 30*15*15 cubic centimeters;
[0108] ② Move 30 asphalt blocks outside and pour one portion of the additive into the crack of one asphalt block;
[0109] ③ The asphalt penetration tester is used to test the surface solidification hardness of the additive, and a person is manually judged whether the surface of the additive is solidified, and the solidification time of the additive is recorded;
[0110] ④ Take the average value of the solidification time data of 5 additives prepared in the same embodiment or comparative example, as shown in Table 1;
[0111] Table 1
[0112] project Surface solidification time Example 1 2h43min Example 2 1h20min Example 3 2h30min Comparative Example 1 3h15min Comparative Example 2 3h40min Comparative Example 3 2h58min
[0113] As can be seen from Table 1, compared with Example 1, Example 3 and Comparative Examples 1-3, Example 2 requires the shortest time for the additive surface to solidify. Therefore, when the additive prepared in Example 2 is used to repair cracks on an asphalt pavement, traffic can be opened to traffic at the fastest speed, thereby minimizing the time for road closures and alleviating the pressure of road congestion.
[0114] 2. Elongation test
[0115] 1.1 Experimental Materials
[0116] Asphalt blocks: 20 (length*width*height: 2*2*2m) (10 asphalt blocks have cracks with length*width*depth: 30*15*15cm on the same surface)
[0117] 1.2 Experimental procedures
[0118] ① Take 5 portions of the additives prepared in Example 2 and Comparative Examples 4-6, each with a volume of 30*15*15 cubic centimeters;
[0119] ② Move 20 asphalt blocks outside and pour one portion of the additive into the crack of one asphalt block;
[0120] ③ The waiting time is 1 day, and then the 20 asphalt blocks (width and height remain unchanged) are cut by a cutting machine to obtain the cross section of the asphalt block;
[0121] ④ Calculate the cross-sectional area of the asphalt block after the additive solidifies;
[0122] ⑤ Take the average value of the cross-sectional area data generated after solidification of 5 portions of the additive prepared in the same embodiment or comparative example, as shown in Table 2;
[0123] Table 2:
[0124] project Cross-sectional area (square centimeters) Example 2 630 Comparative Example 4 430 Comparative Example 5 430 Comparative Example 6 310
[0125] As can be seen from Table 2, compared with Comparative Examples 4-6, the additive prepared in Example 2 has the largest area of penetration and extension into the asphalt through cracks, so that it can be more widely combined with the asphalt, which helps to enhance the penetration ability of styrene-butadiene-styrene block copolymer and surfactant, enhance the overall strength and stability of the repaired area, help to better fill cracks, potholes and other defects, and improve the smoothness and durability of the road.
[0126] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An additive for enhancing the repair ability of asphalt concrete pavement, characterized in that: The raw materials for its preparation include, by weight: 10-15 parts of surface coagulant, 10-15 parts of diathermic wire, 3-9 parts of surfactant, 6-8 parts of antioxidant, 3-6 parts of anti-ultraviolet agent and 30-40 parts of styrene-butadiene-styrene block copolymer.
2. The additive for enhancing the repairing ability of asphalt concrete pavement according to claim 1, characterized in that: The preparation process of the surface coagulant is as follows: In a sealed environment, the anaerobic adhesive solution and the α-cyanoacrylate adhesive solution are stirred and mixed, the stirring speed is controlled to be 10-30 rps, the temperature is controlled to be 10-16° C., and the time is controlled to be 10-15 min to obtain a glue mixture; The pore-increasing powder and the glue mixture are stirred and mixed, the stirring speed is controlled to be 10-30 rps, the temperature is controlled to be 5-10° C., and the time is controlled to be 10-15 min to obtain a surface coagulant.
3. The additive for enhancing the repairing ability of asphalt concrete pavement according to claim 2, characterized in that: The mass ratio of the anaerobic adhesive solution, the α-cyanoacrylate adhesive solution and the pore-increasing powder is 1:6:0.
5.
4. The additive for enhancing the repairing ability of asphalt concrete pavement according to claim 2, characterized in that: The preparation process of the pore-increasing powder is as follows: The slaked lime powder and the sodium hydroxide particles are stirred and mixed, and the stirring speed is controlled to be 10-20 and the time is controlled to be 10-15 minutes; wherein the diameter of the slaked lime powder is 30-60 μm, and the diameter of the sodium hydroxide particles is 1-3 mm, to obtain a pore-increasing powder.
5. The additive for enhancing the repairing ability of asphalt concrete pavement according to claim 4, characterized in that: The mass ratio of the slaked lime powder to the sodium hydroxide particles is 4:
1.
6. The additive for enhancing the repairing ability of asphalt concrete pavement according to claim 1, characterized in that: The preparation process of the diathermic wire is as follows: melting iron powder and copper powder at high temperature to obtain a metal mixture; Pour the graphite fiber into the metal mixture and mix and stir, control the stirring speed to 2-6rps, and control the time to 3-8min to obtain a fiber-metal mixture; The fiber metal mixture is poured into a mold to obtain a composite metal sheet with a thickness of 4-6 μm, and the composite metal sheet is sheared by a fiber shearing machine to obtain a heat-transmitting wire with a diameter of 4-6 μm and a length of 1-3 cm.
7. The additive for enhancing the repairing ability of asphalt concrete pavement according to claim 6, characterized in that: The mass ratio of the iron powder, copper powder and graphite fiber is 2:1:0.
2.
8. A method for preparing an additive for enhancing the repairing ability of asphalt concrete pavement according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing styrene-butadiene-styrene block copolymer and a surfactant to obtain a permeable filler; S2, an antioxidant, an anti-ultraviolet agent and a permeable filler are mixed to obtain a characteristic filler; S3. Mix the surface coagulant, the diathermic wire and the special filler to obtain an additive.